Altered Lipid Profile in COVID-19 Patients and Metabolic Reprogramming - Zhao, Tie; Wang, Chunhui; Duan, Biyan; Yang, Peipei; Wu, Jianguo; Zhang, Qiwei (Frontiers in Microbiology, 2022)
Background: Coronavirus Disease 2019 (COVID-19) is a global pandemic. Previous studies have reported dyslipidemia in patients with COVID-19. Herein, we conducted a retrospective study and bioinformatics analysis to evaluate the essential of the lipid profile as well as the possible mechanism in COVID-19 patients. Methods: First of all, the retrospective study included three cohorts, COVID-19 patients, health examination population and patients with chronic obstructive pulmonary disease (COPD). For each subject, serum lipid profiles in the biochemical data were compared, including triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C). Furthermore, bioinformatics analyses were performed for biological or immunologic mechanism exploration. Results: In line with the biochemical data of the three cohorts, statistical result displayed that the COVID-19 patients were more likely to have lower levels of TC and HDL-C as compared with healthy individuals. The different proteins associated with COVID-19 are involved in lipid pathway, and can target and regulate cytokines and immune cells. Additionally, a heatmap revealed that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections were possibly involved in lipid metabolic reprogramming. The viral proteins, such as Spike (S) and Non-structural protein 2 (Nsp2) of SARS-CoV-2 may be involved in metabolic reprogramming. Conclusion: The metabolic reprogramming post SARS-CoV-2 infections is probably associated with immune and clinical phenotype of patients. Hence, the metabolic reprogramming may be targeted for developing antivirals against COVID-19.